Multimodal Discourse Analysis on A Cartoon Film Trailer Up - Qidan Xing (Journal of Linguistics and Communication Studies, 2022)
This article aims to investigate a cartoon film trailer Up by the multimodal discourse analysis. The highlight of this study is that different elements (e.g., semiotic information) involved in selected film trailer will be analyzed in a detailed way, including sounds, music, images and lines. With this regard, it will provide a general picture about how the film trailer in the context of multimodal discourse performs and conveys the meaningful information to viewers. In addition, there will be further discussions on other dimensions in the film trailer and relevant limitations.